2015
DOI: 10.1364/ol.40.001472
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid M-mode-like OCT imaging of three-dimensional microvasculature in vivo using reference-free processing of complex valued B-scans

Abstract: Received Month X, XXXX; revised Month X, XXXX; accepted Month X, XXXX; posted Month X, XXXX (Doc. ID XXXXX); published Month X, XXXXWe propose a novel OCT-based method for visualizing microvasculature in 3D using reference-free processing of individual complex-valued B-scans with highly overlapped A-scans. In the lateral direction of such a B-scan, the amplitude and phase of speckles corresponding to vessel regions exhibit faster variability, and thus can be detected without comparison with other B-scans recor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 27 publications
0
59
0
2
Order By: Relevance
“…17,18 In addition to the high resolution svOCT imaging of microvasculature, it has potential to provide new insight into the dynamics of vascular remodeling. [19][20][21] In our previous phantom study, 11 we demonstrated that MBs can be used as an optical contrast agent, yielding increased scattering (1.4× at 300 nm and 6× at 850 nm). Similarly, Barton et al 10 have shown that MBs enhanced the backscattered OCT signal in model scattering media.…”
Section: Introductionmentioning
confidence: 86%
“…17,18 In addition to the high resolution svOCT imaging of microvasculature, it has potential to provide new insight into the dynamics of vascular remodeling. [19][20][21] In our previous phantom study, 11 we demonstrated that MBs can be used as an optical contrast agent, yielding increased scattering (1.4× at 300 nm and 6× at 850 nm). Similarly, Barton et al 10 have shown that MBs enhanced the backscattered OCT signal in model scattering media.…”
Section: Introductionmentioning
confidence: 86%
“…This can be accomplished, for example, using conventional procedures of least-squares fitting 24 of the depth-dependent phase-variation within a selected size of the processing window. Before fitting the slope of the axial (vertical) dependence of the phase variation, for every horizontal row of pixels within the processing window, it is useful to determine the average phase variation at that depth, for example, using the Kasai estimator 33,34 or a somewhat different but analogous procedure described below in this section. The least-square procedure 24 of fitting the vertical phase-variation to determine the phase-variation gradient [ Fig.…”
Section: Comparison Of Phase-gradient Estimation Methods For Finding mentioning
confidence: 99%
“…OCT angiography concept implemented in the device is based on the analysis of decorrelation of OCT image speckle pattern induced by blood flow within tissue. 36,37 The device is equipped with the contact probe, and the probe pressure to the tissue was controlled by a custom-designed holder to avoid effects of tissue compression on OCT images. 38 OCT imaging of the target area was performed prior to and immediately after the exposure and in 1, 4, and 7 days after the procedure (in 24, 96, and 168 hours, respectively).…”
Section: Optical Diagnostics Modalitiesmentioning
confidence: 99%